Respectable Citizens: Gender, Family, and Unemployment in Ontario's Great Depression - Campbell, Lara A. (University of Toronto Press, 2009)
High unemployment rates, humiliating relief policy, and the spectre of eviction characterized the experiences of many Ontario families in the Great Depression. Respectable Citizens is an examination of the material difficulties and survival strategies of families facing poverty and unemployment, and an analysis of how collective action and protest redefined the meanings of welfare and citizenship in the 1930s.Lara Campbell draws on diverse sources including newspapers, family and juvenile court records, premiers' papers, memoirs, and oral histories to uncover the ways in which the material workings of the family and the discursive category of 'respectable' citizenship were invested with gendered obligations and Anglo-British identity. Respectable Citizens demonstrates how women and men represented themselves as entitled to make specific claims on the state, shedding new light on the cooperative and conflicting relationships between men and women, parents and children, and citizen and state in 1930s Canada. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/respectablecitiz00camp OCLC: 404612900

Fight Back: Workplace Justice for Immigrants - Choudry, Aziz; Hanley, Jill; Jordan, Steve; Stiegman, Martha; Schragge, Eric (Fernwood, 2009)
[D]ocuments the struggles of immigrant workers and analyses them within the context of neoliberal globalization and the international and national labour markets. Fight Back grew out of collaboration between a group of university-affiliated researchers who are active in different social movements and community organizations in partnership with the Immigrant Workers Centre in Montreal. The book shares with us the experiences of immigrant workers in a variety of workplaces. It is based on the underlying belief that the best kind of research that tells “how it really is” comes from the lived experience of people themselves. – Publisher's description. Contents: Introduction – Context – Making immigrant workers – Access to social rights for migrants to Canada: the long divide between the law and the real world – Seasonal agricultural workers – Canada's live-in caregiver program : popular among both employers and migrants, but structured for dependency and inequality – Survival and fighting back.
http://fernwoodpublishing.ca/book/fight-back
Keywords: Canada; Canada. Immigrants; Conditions économiques. Immigrants; Economic conditions. Immigrants; Employment; Immigrants; Social conditions. Immigrants; Travail

Philippe Vaillancourt : militant syndical et politique - Comby, Marc (VLB, 2009)
Philippe Vaillancourt (1913-1984) est venu à l'action syndicale par la politique et, durant toute sa carrière, il a conjugué ces deux formes d'engagement. Amorcé pendant la Grande Crise pour se terminer pendant la Révolution tranquille, le parcours militant de Philippe Vaillancourt a été particulièrement ardu, en butte entre autres à l'opposition du gouvernement de Maurice Duplessis. Suivre Philippe Vaillancourt dans cette période pionnière, c'est revivre des conflits du travail souvent violents, c'est suivre l'histoire des rivalités et des regroupements de syndicats, des tentatives de ces derniers de créer un parti ouvrier en s'alliant avec la Cooperative Commonwealth Federation (CCF), puis avec le Nouveau Parti Démocratique (NPD), de T.C. Douglas. Fermement convaincu de l'importance de l'éducation syndicale, Philippe Vaillancourt a consacré à cette priorité les dernières années de sa carrière au Congrès canadien du travail (CCT) pour le Québec, dont est membre la Fédération des travailleurs du Québec (FTQ). –Résumé de l'éditeur
Keywords: Vaillancourt; Philippe; 1913-1984

Games of Empire: Global Capitalism and Video Games - Dyer-Witheford, Nick; De Peuter, Greig (University of Minnesota Press, 2009)
In the first decade of the twenty-first century, video games are an integral part of global media culture, rivaling Hollywood in revenue and influence. No longer confined to a subculture of adolescent males, video games today are played by adults around the world. At the same time, video games have become major sites of corporate exploitation and military recruitment. In Games of Empire, Nick Dyer-Witheford and Greig de Peuter offer a radical political critique of such video games and virtual environments as Second Life, World of Warcraft, and Grand Theft Auto, analyzing them as the exemplary m
Available at Internet Archive to readers with print disabilities: https://archive.org/details/gamesofempireglo0000dyer OCLC: 659579816
Keywords: Capitalism Social aspects; Computerspiel; GAMES Video & Electronic; Imperialism Social aspects; Impérialisme Aspect social; Jeux vidéo Aspect social; Jeux vidéo Aspect économique; Tv-spel ekonomiska aspekter; Tv-spel sociala aspekter; Video games Economic aspects; Video games Social aspects; Wirtschaft

Unions, Equity, and the Path to Renewal - Foley, Janice R.; Baker, Patricia L. (UBC Press, 2009)
Trade unions in Canada are losing their traditional support base, and membership numbers could sink to US levels unless unions recapture their power. Unions, Equity, and the Path to Renewal brings together a distinguished group of union activists and equity scholars who trace how traditional union cultures, practices, and structures have eroded solidarity and activism and created an equity deficit in Canadian unions. Informed by a feminist vision of unions as instruments of social justice, the contributors argue that equity within unions is not simply one possible path to union renewal – it is the only way to reposition organized labour as a central institution in workers’ lives. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/unionsequitypath0000unse
Keywords: Canada; Equality; Labor unions; Social aspects; Women in the labor movement

The Prestige Squeeze: Occupational Prestige in Canada Since 1965 - Goyder, John (McGill-Queen's University Press, 2009)
How Canadians rate the prestige of their occupations, and what this says about our understanding of the knowledge economy, social mobility and inequality, and our working selves. "What do you do?" is often the first question posed when strangers meet, as occupation reveals a great deal about both social identity and social standing or "occupational prestige." Sociologists have studied occupational prestige for decades, including a landmark national survey in 1965 by Peter Pineo and John Porter. John Goyder updates Pineo and Porter's work, providing a detailed comparison of their results with a similar national scale survey conducted in 2005. The results challenge the accepted view that prestige ratings are constant over time and across societies. Goyder shows that there have been some surprising changes in these ratings: instead of the expected premium on jobs in the knowledge sector, more traditional occupations - such as the skilled trades, even if they require little education or pay a low wage - have gained the most prestige. There has been a significant decrease in consensus about occupational prestige ratings and the tendency for respondents to upgrade the prestige of their own occupation is much more pronounced in the recent data. Goyder argues that these changes are a sign of the shifting nature of values in a meritocratic society in which increasing income inequality is a growing reality. Results from prestige surveys help in the construction of socio-economic scales for occupations and inform career counselling for young people and negotiations by labour unions and associations. "The Prestige Squeeze" goes beyond this to question the very nature of how we measure social equality and mobility. –Publisher's description
Book available at Internet Archive to readers with print disabilities: https://archive.org/details/prestigesqueezeo0000goyd

Canadian Labour and Employment Relations - Gunderson, Morley; Taras, Daphne Gottlieb (Pearson Addison Wesley, 2009)
Contents: Canadian labour and employment relations / Daphne G. Taras and Morley Gunderson – Understanding the unionization decision / Ann C. Frost and Daphne G. Taras – Labour history and the development of modern capitalism / Richard Marsden – Unions : membership, structures, actions and challenges / Gregor Murray – The management of industrial relations / Mark Thompson – Managing the high-involvement workplace / Anil Verma and Daphne G. Taras – Social, political, and economic environments / Frank Reid and Rafael Gomez – Collective bargaining legislation in Canada / Sara Slinn – The individual employment contract and employment / Geoffrey England – Collective bargaining : structure, process, and innovation / Richard Chaykowski – The collective agreement / Anthony Giles and Akivah Starkman – Strikes and dispute resolution / Morley Gunderson, Bob Hebdon, and Douglas Hyatt – The grievance arbitration process and workplace / Kenneth Wm. Thornicroft – Union impact on compensation, productivity, and management of the organization / Morley Gunderson and Douglas Hyatt – Public-sector collective bargaining / Mark Thompson and Patrice Jalette – Union-management relations in Québec / Esther Déom and Jean-Noël Grenier with Marie-Pierre Beaumont – Trade unions and labour relations regimes: international perspectives in a globalizing world / Carla Lipsig-Mummé. Previous eds. published under title: Union-management relations in Canada; Includes bibliographical references and index.
Keywords: Industrial relations – Canada – Textbooks

Laying It on the Line: Driving a Hard Bargain in Challenging Times - Hargrove, Buzz (HarperCollins, 2009)
In late 2008, the world’s economy began to tumble at avalanche speed, and at the forefront of the manufacturing collapse were the Big Three automakers: Chrysler, General Motors and Ford. For decades, these companies had been shining stars, providing billions of dollars of new investments and thousands of well-paying jobs. Yet suddenly the heads of these and other manufacturing giants found themselves begging governments for financial packages to save their industries. What the hell happened? Buzz Hargrove, the former head of the Canadian Autoworkers (CAW), retired right before the collapse, but not before witnessing the decades of bad decisionmaking— by federal governments and CEOs—that set the stage for the sudden crisis. No one knows the ins and outs of manufacturing like Hargrove, a man who championed the cause of on-the-line workers but who also earned the immense respect of political and business leaders. In Laying It on the Line, Hargrove explains the crisis from his side of the table, what it means for Canada and how the manufacturing sector can again become this country’s foremost economic driver. Along the way, he shares the behind-the-door dealings with GM, Ford, Air Canada and others, explaining the controversial agreements he reached over his decades as Canada’s chief labour leader. Laying It on the Line is a timely call to arms for industry, governments and indeed all Canadians. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/layingitonlinedr0000harg/page/n5/mode/2up
Keywords: 20th century; 21st century; Automobile industry History; Automobile industry and trade; Canada; Collective labor agreements; Hargrove; Buzz; History; Industrial relations; Manufacturing industries

Rig: An Oral History of the Ocean Ranger Disaster - Heffernan, Mike (Creative Publishers, 2009)
In the early hours of February 15, 1982, tragedy struck the Ocean Ranger oil rig when it capsized and sank in a severe weather storm 170 nautical miles east of St. John's, Newfoundland. All of the eighty-four crewmen perished, including fifty-six men from the province. This was Canada's greatest maritime disaster since World War II. Rig is a powerful story filled with first-person accounts and previously unpublished photographs. In an intimate journey through grief and sadness, Rig searches for reconciliation among the victims' families and those who risked their own lives to help those on the Ocean Ranger. –Publisher's description
Keywords: Ocean Ranger (Drilling rig)

Canadian Maverick: The Life and Times of Ivan C. Rand - Kaplan, William (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2009)
Ivan Rand had a long, varied and remarkable career. He is best known for his Supreme Court of Canada judgments in a series of cases emanating from Quebec in the 1950s and dealing with civil rights, cases which established limits on the government’s ability to persecute unpopular religious minorities. To labour lawyers he is also an icon for his invention of the ‘Rand formula’, one of the defining features of Canadian labour law. Rand was also a member of the United Nations special committee on Palestine in 1947, the founding Dean of the University of Western Ontario law school, and three times a royal commissioner, looking into the problems of the Canadian coal industry, the misconduct of Mr. Justice Leo A. Landreville, and labour disputes in Ontario. In this thoroughly researched and fast-paced book, William Kaplan traces Rand’s life and career in all its richness and controversy – Rand as lawyer, politician, judge, dean, and royal commissioner – through many seminal events of the twentieth century in Canada. The Rand that emerges is variously inspiring, frustrating to understand, sometimes contradictory, always complex. –Publisher's description

Essex County: A Graphic Novel - Lemire, Jeff. (Top Shelf Productions, 2009)
Where does a young boy turn when his whole world suddenly disappears? What turns two brothers from an unstoppable team into a pair of bitterly estranged loners? How does the simple-hearted care of one middle-aged nurse reveal the scars of an entire community, and can anything heal the wounds caused by a century of deception? Award-winning cartoonist Jeff Lemire pays tribute to his roots with Essex County, an award-winning trilogy of graphic novels set in an imaginary version of his hometown, the eccentric farming community of Essex County, Ontario, Canada. In Essex County, Lemire crafts an intimate study of one community through the years, and a tender meditation on family, memory, grief, secrets, and reconciliation. With the lush, expressive inking of a young artist at the height of his powers, Lemire draws us in and sets us free. This new edition collects the complete, critically-acclaimed trilogy (Tales from the Farm, Ghost Stories, and The Country Nurse) in one deluxe volume! Also included are over 40-pages of previously unpublished material, including two new stories. This title has been voted by Canada Reads Top 10 title for the decade! –Publisher's description
Keywords: Blue-collar work; Farming community; Nurse; Ontario Essex; Sabotage

The Factory Voice - Lynes, Jeanette (Coteau Books, 2009)
Wrapped around the stories of these four women, is a mystery. Something''s gone wrong with the Mosquitos being built for the war effort – they keep crashing in flight tests, for no apparent reason. Is the problem with their design, or are they being sabotaged? By whom? The traitorous Red Finns? The political subversives who have recently escaped from one of the nearby prison camps? Everyone''s on high alert, and "The Factory Voice" keeps abreast of the details. Or at least the rumours. –Publisher's description
OCLC: 303029307
Keywords: 1939-1945; Airplane factories; Airplane factories Fiction; Amitié féminine Romans; nouvelles; etc; Avions Usines Romans; nouvelles; etc; Canada; Female friendship; Female friendship Fiction; Fiction; Guerre mondiale; 1939-1945 Femmes Romans; nouvelles; etc; Historical fiction; Northern Ontario; Ontario; Northern Fiction; Women; World War; 1939-1945 Canada Fiction; World War; 1939-1945 Women Fiction

The Guy in the Green Truck: A Biography of John St. Amand - McCrorie, James Napier (Roseway/Fernwood, 2009)
Affectionate portrait of John St. Amand (1943-2007) who, under the tutelage of the left-wing labour activist, Madeleine Parent, moved in 1981 from Ontario to Nova Scotia to become a union organizer.
Keywords: History; Labor Unions; Officials and employees; Organizing; St. Amand; John; 1943-2007

Labour Pains: Thunder Bay's Working Class in Canada's Wheat Boom Era - Morrison, Jean; Thunder Bay Historical Museum Society (Thunder Bay Historical Museum Society, 2009)
Through painful struggles and changing relationships, Thunder Bay’s working class defined itself during the tumultuous years before World War I. Labour Pains looks at many responses to the harshness of industrialism: trade unionism and labour politics, unrest and violence, the Social Gospel and socialism, mediation and conciliation. Alliances and conflict, many ethnicities and various expressions of class consciousness all contributed to the making of the working class whose members and defenders embraced many remarkable individuals, known and unknown. –Publisher's description. Contents: The beginnings of Thunder Bay's working class [Thunder Bay, Northwestern Ontario] – Trade unions, municipal ownership & labour politics : Harry Bryan and the advent of organized labour] – Dock workers, immigrants and the railways – Socialism, the social gospel and labour politics [labor] – The 1909 Freight Handlers Strike – Who won the 1909 strike? – Labour, socialists and the 1912 Coal Handlers Strike – The Justice system, immigrants and waterfront strikes : socialists and violence – The 1913 Street Railwaymen's Strike – Reformers and rebels, good deeds and discord – Appendix A. Labour unions in Port Arthur and Fort William in 1910. Includes bibliographical references (p. 170-174) and index.
Keywords: History; Labor unions; Ontario; Strikes and lockouts; Thunder Bay; Ont.; Working class

The National Farmers Union: Working for Farm Families for 40 Years. - National Farmers Union (Canada) (National Farmers Union, 2009)
The NFU was formed in 1969 through a merger of the Saskatchewan Farmers Union, the Ontario Farmers Union, the Farmers Union of British Columbia, and the Farmers Union of Alberta. In addition to these provincial unions, farmers from the Maritime provinces—not organized into farmers’ unions at the time—also became part of the NFU structure. Prior to ’69, these provincial unions each had worked autonomously in its respective province, but increasingly they were finding themselves at a disadvantage in attempting to work with the federal government. In an effort to solve that problem, the unions created a coordinating body, the National Farmers Union Council, consisting of representatives of the executives of each provincial union and representatives from the Maritime provinces. Over time, the officials and members from the provincial unions and the Maritimes realized that the major policy decisions affecting farmers were being made at the federal level. At a joint meeting of the executives of the provincial unions and others in Winnipeg in March 1968, the executive members passed a motion to strike a committee to develop a constitution for a direct membership national farm organization. The founding convention of the National Farmers Union was held in Winnipeg in July 1969. In the following months the provincial unions were phased out and their assets and liabilities transferred to the national organization. –Publisher's description
OCLC: 816820748

Harvest Pilgrims: Mexican and Caribbean Migrant Farm Workers in Canada - Pietropaolo, Vincenzo (Between the Lines, 2009)
Like migratory birds, most of Canada’s 20,000 “guest” farm workers arrive in the spring and leave in the autumn. Hailing primarily from Mexico, Jamaica, and smaller countries of the Caribbean, these temporary workers have become entrenched in the Canadian labour force and are the mainstay of many traditional family farms in Canada. Many of them make the trip year after year after year.Vincenzo Pietropaolo has been photographing guest workers and recording their stories since 1984 – in the process travelling to forty locations throughout Ontario and to their homes in Mexico, Jamaica, and Montserrat. The resulting photographs have been highly acclaimed internationally through many publications and exhibitions, including a travelling show curated by the Canadian Museum of Contemporary Photography that opened in Mexico City.With a foreword by Naomi Rosenblum, this beautiful and timely book of photography and exposition aims to shed light on a subject about which many Canadians know all too little. –Publisher's description

Neighbours and Networks: The Blood Tribe in the Southern Alberta Economy, 1884-1939 - Regular, W. Keith (William Keith) (University of Calgary Press, 2009)
[E]xplores the economic relationship that existed between the Blood Indian reserve and the surrounding region of southern Alberta between 1884 and 1939. The Blood tribe, though living on a reserve, refused to become economically isolated from the larger community and indeed became significant contributors to the economy of the area. Their land base was important to the ranching industry. Their products, especially coal and hay, were sought after by settlers, and the Bloods were encouraged, not only to provide them as needed, but also to become expert freighters, transporting goods from the reserve for non-Native business people. Blood field labor in the Raymond area sugar beet fields was at times critical to the functioning of that industry. In addition, the Bloods' ties to the merchant community, especially in Cardston and Fort Macleod, resulted in a significant infusion of money into the local economy. Regular's study fills the gap left by Canadian historiography that has largely ignored the economic associations between Natives and non-Natives living in a common environment. His microhistory refutes the perception that Native reserves have played only a minor role in regional development and provides an excellent example of a cross-cultural, co-operative economic relationship in the post-treaty period on the Canadian plains. –Publisher's description. Contents: Introduction – 'Free Range or Private Property': Integrating Blood Reserve Land into the Non-Native Economy – 'Selling to Outsiders': Marketing Coal, Hay, and Freighting Services – 'All the Indians Have Gone to the Beet': Blood Labour in the Raymond Sugar Beet Fields – 'A Prospective Citizen of No Mean Importance': The Bloods and the Business Community – Conclusion: Change Over Time.
http://uofcpress.com/books/9781552382431
Keywords: Alberta; Blood Indian Reserve No. 148 (Alta.); Commerce; Economic conditions; History; Indian business enterprises; Kainah Indians

Regulating Flexibility: The Political Economy of Employment Standards - Thomas, Mark P. (McGill-Queen's University Press, 2009)
In a contemporary labour market that includes growing levels of precarious employment, the regulation of minimum employment standards is intricately connected to conditions of economic security. With a focus on the role of neoliberal labour market policies in promoting "flexible" employment standards legislation - particularly in the areas of minimum wages and working time - Mark Thomas argues that shifts toward "flexible" legislation have played a central role in producing patterns of labour market inequality. Using an analytic framework that situates employment standards within the context of the broader social relations that shape processes of labour market regulation, Thomas constructs a case study of employment standards legislation in Ontario from 1884 to 2004. Drawing from political economy scholarship, and using a qualitative research methodology, he analyses class, race, and gender dimensions of legislative developments, highlighting the ways in which shifts towards "flexible" employment standards have exacerbated longstanding racialized and gendered inequities. Regulating Flexibility argues that in order to counter current trends towards increased insecurity, employment standards should not be treated as a secondary form of labour protection but as a cornerstone in a progressive project of labour market re-regulation. –Publisher's description
Book available at Internet Archive to people with print disabilities: https://archive.org/details/regulatingflexib0000thom

Gender and the Contours of Precarious Employment - Vosko, Leah F.; MacDonald, Martha; Campbell, Iain (Routledge, 2009)
Precarious employment presents a monumental challenge to the social, economic, and political stability of labour markets in industrialized societies and there is widespread consensus that its growth is contributing to a series of common social inequalities, especially along the lines of gender and citizenship. The editors argue that these inequalities are evident at the national level across industrialized countries, as well as at the regional level within federal societies, such as Canada, Germany, the United States, and Australia and in the European Union. This book brings together contributions addressing this issue which include case studies exploring the size, nature, and dynamics of precarious employment in different industrialized countries and chapters examining conceptual and methodological challenges in the study of precarious employment in comparative perspective. The collection aims to yield new ways of understanding, conceptualizing, measuring, and responding, via public policy and other means - such as new forms of union organization and community organizing at multiple scales - to the forces driving labour market insecurity. –Publisher's description
OCLC: 305411805
Keywords: Alemania; Allemagne; Analyse comparative; Arbeitsmarkt; Arbetsmarknad genusaspekter; Australia; Australie; Canada; Canadá; Contract system (Labor); Espagne; España; Estados Unidos; Etats-Unis; Etats-Unis d'Amérique; Fackligt arbete; France; Francia; Frau; Genre; Germany; Inégalités sociales; Ireland; Irlanda; Irlande; Japan; Japon; Japón; Marché du travail; Netherlands; Niedriglohn; Pays développés; Pays-Bas; Países Bajos; Precarious employment; Précarité; Reino Unido de Gran Bretaña e Irlanda del Norte; Royaume-Uni de Grande-Bretagne et d'Irlande du Nord; Rörlighet på arbetsmarknaden; Sexual division of labor; Spain; Suecia; Suède; Sweden; Temporary employment; Travail précaire; Travail temporaire; UE/CE Etats membres; USA; United Kingdom of Great Britain and Northern Ireland; Women Employment; Zeitarbeit; chômage; desempleo; division du travail basée sur le sexe; división del trabajo por sexo; empleo a tiempo parcial; empleo precario; empleo temporal; emploi précaire; emploi temporaire; emploi à temps partiel; men workers; part time employment; precarious employment; sexual division of labour; temporary employment; trabajadoras; trabajadores masculinos; travailleurs masculins; travailleuses; unemployment; women workers

If You're in My Way, I'm Walking: The Assault on Working People since 1970 - Workman, W. Thom (Fernwood Pub., 2009)
“If you’re in my way I’m walking.” This arrogant statement by former Prime Minister Jean Chrétien on the occasion of his physical altercation with a protester in Hull, Quebec in the mid-1990s symbolizes the spirit of the relentless drive of capital to rewrite the historical compromise reached with working people after World War II. This early post-war compromise—sometimes referred to as the Fordist Compact—was associated with improving wages and rising living standards for working people. But in recent decades those achievements of the working class are being deliberately rolled back. Workman surveys many features of this experience: changing public perceptions of working life, the deregulation of labour law, the decline in unionization rates, the eclipse of union militancy, the stagnation of real wages, the disproportionate absorption of women into the low-wage sphere and the dismantling of social policy. He demonstrates the unravelling of the post-war compact and its replacement with a far more ex-ploitative relationship between capital and labour. He also points to the decline of the Canadian left and its inability to counter the capitalist onslaught effectively. Nevertheless, there are reasons to be hopeful. Workman calls for a rebuilding of the left through the restoration of left culture. To do this he says that the left must “quit politics,” work to promote the collective memory of working-class achievements, create venues to listen to working people in today’s economy, reject nationalism outright and encourage the labour movement to exploit its disruptive capacity. This revitalized left will form the basis of a deepening social critique, the political lessons of which will prove to be invaluable for working people in the long run. – Publisher's description
http://fernwoodpublishing.ca/book/if-youre-in-my-way-im-walking
Keywords: Labor Unions; Labor movement; Neoliberalism; Right and left (Political science); Working class

Political Trials and Security Measures, 1840-1914 - Wright, Barry; Binny, Susan (Published for the Osgoode Society for Canadian Legal History by University of Toronto Press, 2009)
This third volume of the Osgoode Society’s Canadian State Trials series covers the period from the 1840s to the First World War. It examines a range of political trials as traditionally defined, including those arising from the Fenian invasions and the North-West Rebellions. The volume also expands the definition of state trials to include studies on the early development of secret policing and the evolution of the legal regulation of riot and public order. The editors have assembled a team of experts from across the country in a variety of fields, and produced a comprehensive and fascinating set of studies of the use of law to control political dissent and public disorder.–Publisher's description.
Book available at Internet Archive to people with print disabilities: http://archive.org/details/politicaltrialss0003unse
Keywords: Political crimes and offenses – Canada – History

Why Unions Matter - Yates, Michael (Monthly Review Press, 2009)
In this new edition the author shows why unions still matter. Unions mean better pay, benefits, and working conditions for their members; they force employers to treat employees with dignity and respect; and at their best, they provide a way for workers to make society both more democratic and egalitarian. The author uses both data, and examples to show why workers need unions, how unions are formed, how they operate, how collective bargaining works, the role of unions in politics, and what unions have done to bring workers together across the divides of race, gender, religion, and sexual orientation. The new edition not only updates the first, but also examines the record of the New Voice slate that took control of the AFL-CIO in 1995, the continuing decline in union membership and density, the Change to Win split in 2005, the growing importance of immigrant workers, the rise of worker centers, the impacts of and labor responses to globalization, and the need for labor to have an independent political voice, and the Employee Free Choice Act. –Publisher's description
OCLC: 276816793
Keywords: Labor unions; Labor unions United States; United States